Mechanized No-till Planting For Climate-Smart Agriculture - Matin, M. A.; Mulundu, S; Zingwari, O. (2025)
No-till or direct seeding is a conservation agriculture practice that allows planting seeds through the crop residues without plowing the soil. In Zambia, this is commonly done manually by the smallholder farmers using hand hoes or dibbling sticks to dig planting basins or holes. The basins are then hand planted and fertilized (often again by making holes for fertilizer). The practice has many benefits, including reduced soil erosion and increased infiltration and soil moisture retention. Despite the benefits, a few farmers in the country have adopted it mainly due to the drudgery associated with manual practice. The SIFAZ project has addressed this challenge by introducing a mechanized no-till planter powered by a two-wheel tractor. The double-row planter can be used to plant most crops that are planted in 45 to 90 cm rows. The planter is suitable for planting a sole crop or strip crops in untilled or tilled soil.